LINGUISTIC AND CULTURAL STUDIES IN CLASSES OF GERMAN - Olena Beresten (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2019)
Linguistic and cultural studies are an integral part of learning a foreign language. Language cannot be studied without learning culture, history, geography, traditions, people’s preferences in food, clothing and their behaviour. Each lesson in a foreign language is a lesson in country studies as well. The article presents the methodological development of German language classes including cultural material. The first task includes students splitting into pairs and receiving cards naming either attractions or architectural objects, or famous personalities, or a German brand. They come to the map and get as much necessary information as possible. Then they present the acquired knowledge in the form of a plenary session. The second task requires the students to use a computer in search for more detailed information about the life and work of prominent people of German origin. At the end of their search work, we split students into pairs for an unprepared dialogue. The idea is to get absolutely random pairs. So, the task is to get as much interesting information from the partner in the conversation as possible. Then the person, gathering the information about a famous person, without naming him or her, is chosen. The rest of the students pose him questions requiring an answer “yes” or “no,” and try to guess the name of the person. The interactive tasks offered have an aim of teaching the students to “extract” information on a given topic independently, using various sources such as a map, the Internet, an interlocutor. The information obtained is reinforced in practice, i.e. it is included in speech in the form of dialogues, interviews, questions. The teacher performs an advisory and guiding function in the performance of these tasks. Such elements of “independence” raise students’ confidence and create an imitation of fulfilling real tasks. This approach prepares students for their future professional life and forms the necessary skills for making independent decisions. It is possible to present the results of the search work in an interesting way and at the end of the lesson place them either on a magnetic board or on a rope with the help of clothespins so that students can summarize their activities. The development perspective of this approach is the methodological inclusion of presentations on cross-cultural topics made by students in the course of the lesson.